Searching antibodies for gelsolin amyloidosis: discovery and optimization of anti-AGelD187N antibodies - Leimu, Laura (fi=Turun yliopisto|en=University of Turku|, 2025)
Protein-misfolding diseases comprise a large and growing group of human disorders. Their common feature is that a protein or part of it begins to aggregate unnaturally in the body, causing different clinical manifestations. Gelsolin amyloidosis is a hereditary systemic protein-misfolding disease caused by a point mutation in the gelsolin gene. As a result of the mutation, plasma gelsolin is proteolytically cleaved and an amyloidogenic fragment of plasma gelsolin, AGelD187N, is formed. AGelD187N aggregates in different organs, leading to ophthalmological, neurological, cutaneous, and oral symptoms starting from young adulthood. As with most protein-misfolding diseases, only symptomatic treatments are available for gelsolin amyloidosis, highlighting a significant need for disease-modifying therapy. In this study, antibody fragments were discovered that inhibited the pathological aggregation of AGelD187 efficiently in vitro. First, an aggregation assay was developed, in which the aggregation process of AGelD187N from monomers to amyloid fibrils could be monitored on a scale that allowed the evaluation of the functional impact of potential aggregation inhibitors. Next, AGelD187N-binding antibody fragments isolated from synthetic libraries using phage display technology were evaluated in the assay. All tested antibody fragments reduced AGelD187N aggregation, and two blocked it completely. After the conversion of the most promising antibody fragment as a full-length antibody, the colloidal stability of the antibody was improved using mammalian display technology. The high colloidal stability of the antibody allows it to be developed into a subcutaneous drug product that requires high antibody concentrations. The fully human and drug-like anti-AGelD187N antibodies presented in this study may provide a promising starting point for a disease-modifying treatment for gelsolin amyloidosis. Before that, the bioavailability and functional effect of the developed antibodies need to be studied in a transgenic mouse model. However, the antibodies presented in this study can already be used in fundamental research on gelsolin amyloidosis and as diagnostic tools for the disease.